1980
DOI: 10.1001/archpedi.1980.02130220042013
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Transmission of Bacteriophage Type 7/11/12 Group B Streptococci in a Special Care Nursery

Abstract: \s=b\Two premature infants in a special care nursery acquired late-onset group B streptococcal (GBS) sepsis within a 24\ x=req-\ hour period. The infecting strains were serotype III organisms with bacteriophage type 7/11/12. Cultures of the mothers of the two affected infants were negative for GBS, implying nosocomial acquisition of infection. Although 32% of nursery personnel had mucosal carriage of GBS, none of the seven isolates of GBS type III was the same bacteriophage type as the two infecting strains. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…33 , 37 Five references suggested transmission via healthcare workers, 25 , 27 , 29 , 33 , 39 , 42 Boyer et al found that overall GBS carriage among nursery staff at the time of the cluster was 34% (18/53), comprising rectal (16/18), vaginal (13/18) and throat (3/18) carriage. 25 Whilst none of the staff isolates matched the phage type identified in the two cluster cases, a culture survey conducted one month later found 4/15 infants colonized with a phage type carried by 3 staff at the time of the cluster. Steere et al reported that 41% (11/27) of staff who had direct contact with cluster cases were GBS-positive (throat, vaginal or urethral, and rectal swabs), of whom 4 had the cluster serotype.…”
Section: Late-onset Disease Clustersmentioning
confidence: 92%
“…33 , 37 Five references suggested transmission via healthcare workers, 25 , 27 , 29 , 33 , 39 , 42 Boyer et al found that overall GBS carriage among nursery staff at the time of the cluster was 34% (18/53), comprising rectal (16/18), vaginal (13/18) and throat (3/18) carriage. 25 Whilst none of the staff isolates matched the phage type identified in the two cluster cases, a culture survey conducted one month later found 4/15 infants colonized with a phage type carried by 3 staff at the time of the cluster. Steere et al reported that 41% (11/27) of staff who had direct contact with cluster cases were GBS-positive (throat, vaginal or urethral, and rectal swabs), of whom 4 had the cluster serotype.…”
Section: Late-onset Disease Clustersmentioning
confidence: 92%
“…A newly developed bacteriophage typing system consisting of 24 phages provides a far higher degree of discrimination3 and has been used to study the spread of group B streptococci within a nursery4 and a special-care baby unit. 5 Aber et al suggested that nosocomial transmission of group B streptococci in the nursery is an important cause of neonatal-colonisation. 6 We studied babies in two postnatal wards and the special-care baby unit at this hospital over six months to assess the incidence of acquisition of group B streptococci in babies after birth, to study the epidemiology of colonisation of group B streptococci among both babies and staff in the special-care baby unit, to document specific instances of nosocomial transmission, and to assess the effectiveness of measures designed to prevent this mode of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal compli-cations during labor play a less important role in lateonset disease, compared with that in early-onset disease [1]. Evidence supports nosocomial acquisition [4][5][6][7][8][9] or transmission of GBS through breast milk [10][11][12][13]. Others have reported hospitalization [14] or human immunodeficiency virus (HIV) infection [15] as risk factors for late-onset GBS disease.…”
mentioning
confidence: 99%